Murder in galway eaudiobook - O'Connor, Carlene (Home to Ireland Mystery, 2020)
New Yorker Tara Meehan's first trip to Galway may be her last ... Tara never imagined her introduction to Ireland like this—carrying her mam's ashes to honor her final request: "Tell Johnny I'm sorry ... Take me home." She's never met her mam's estranged brother, Johnny Meehan, who owns an architectural salvage business in Galway. Although Tara is immediately charmed by the medieval city, the locals seem wary of strangers and a gypsy warns her that death is all around. When Tara arrives at her uncle's stone cottage, the prophesy seems true. A dead man lies sprawled over the threshold in a pool of blood. The victim turns out to be Johnny's wealthiest client, and her missing uncle is the garda's numberone suspect. In trying to find Johnny and solve the crime, Tara uncovers her mam and uncle's troubled past. But with a desperate killer about, she had better mind herself, or they'll be tossing her ashes in Galway Bay ...